2018
DOI: 10.1016/j.rse.2017.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Eddy-induced cross-shelf export of high Chl-a coastal waters in the SE Bay of Biscay

Abstract: Different remote sensing data were combined to characterise a winter anticyclonic eddy in the southeastern Bay of Biscay and to infer its effects on cross-shelf exchanges, in a period when typical along shelf-slope currents depict a cyclonic pattern. While the joint analysis of available satellite data (infrared, visible and altimetry) permitted the characterisation and tracking of the anticyclone properties and path, data from a coastal HF radar system enabled a quantitative analysis of the surface cross-shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 66 publications
0
42
0
Order By: Relevance
“…Various responses in phytoplankton biomass and productivity have also been documented at eddy peripheries in relation to stronger vertical velocities, enhanced mixing, as well as advection and entrainment (Lévy et al, ; Mahadevan, ; Quartly & Srokosz, ). However, in Eastern Boundary Upwelling Systems, mesoscale eddies are often observed to have a negative impact, with mixing and stirring (Rossi et al, , ; Y. Wang et al, ), as well as offshore transport and subduction of biomass (Rubio et al, ; Y. Wang et al, ) and nutrients (Gruber et al, ), resulting in a reduction of phytoplankton biomass and production in shelf regions. Since we investigated seasonal means of Chla and phytoplankton size classes, we could not examine the direct impacts of mesoscale features in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various responses in phytoplankton biomass and productivity have also been documented at eddy peripheries in relation to stronger vertical velocities, enhanced mixing, as well as advection and entrainment (Lévy et al, ; Mahadevan, ; Quartly & Srokosz, ). However, in Eastern Boundary Upwelling Systems, mesoscale eddies are often observed to have a negative impact, with mixing and stirring (Rossi et al, , ; Y. Wang et al, ), as well as offshore transport and subduction of biomass (Rubio et al, ; Y. Wang et al, ) and nutrients (Gruber et al, ), resulting in a reduction of phytoplankton biomass and production in shelf regions. Since we investigated seasonal means of Chla and phytoplankton size classes, we could not examine the direct impacts of mesoscale features in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in Eastern Boundary Upwelling Systems, mesoscale eddies are often observed to have a negative impact, with mixing and stirring (Rossi et al, 2008(Rossi et al, , 2009Y. Wang et al, 2018), as well as offshore transport and subduction of biomass (Rubio et al, 2018;Y. Wang et al, 2018) and nutrients (Gruber et al, 2011), resulting in a reduction of phytoplankton biomass and production in shelf regions.…”
Section: 1029/2018jc014334mentioning
confidence: 99%
“…Recent studies have demonstrated the use of this land‐based remote sensing technology for ocean dynamics in coastal oceanography. Rubio et al (2018) used high‐frequency radar to analyze eddy‐induced high chlorophyll‐a concentrations in the Bay of Biscay. Combining radar and satellite altimetry data further helps in understanding the current dynamics within the bay.…”
Section: Methodsmentioning
confidence: 99%
“…The value of improved altimeter data in detecting coastal SSHa sea level anomalies due to river discharge has been demonstrated by Gómez-Enri et al (2017) and appears promising to study linkages between the land-sea domains (Piecuch et al, 2018). Another example of application concerns the characterization of mesoscale coastal dynamics in the southeastern Bay of Biscay (Spain) in combination with other remote sensing platforms and High-Frequency Radar observations (Rubio et al, 2018).…”
Section: Level 3 Altimetry Datasetsmentioning
confidence: 99%